World archaeology at the Pitt Rivers Museum : a characterization - Hicks, Dan, 1972-; Stevenson, Alice (Archaeopress, 2013)
'World Archaeology at the Pitt Rivers Museum' introduces the range, history and significance of the archaeological collections of the Pitt Rivers Museum, Oxford. In 29 newly-commissioned essays written by a specialist team, the volume explores more than 136,000 artefacts from 145 countries, from the Stone Age to the modern period, and from England to Easter Island. Pioneering a new approach in museum studies, this landmark volume is an essential reference work for archaeologists around the world, and a unique introduction to the archaeological collections of one of the world's most famous museums.